Word Search Puzzle Games - Based Vocabulary Learning: An Action Research to Junior High School in Bengkayang - Septriana Afra; Abdul Arif; Sahrawi Sahrawi (IKIP PGRI Pontianak, 2023)
This research aims to find out how the Word Search Puzzle (WSP) game can improve students' vocabulary mastery. The research was conducted through a Classroom Action Research (CAR) design. The subjects of this research were 30 students in class VIII of SMP Borneo Bengkayang. The data were gathered through observation and measurement techniques, and the data collection tools used were observation checklists, field notes, and vocabulary tests. Then the quantitative data were analyzed using descriptive statistics, while the qualitative data were analyzed using thematic analysis. The results of this research show that WSP game could improve students' vocabulary mastery. WSP helped improve students’ vocabulary mastery in finding out the correct meaning of words, correct spelling, classifying word classes, using words in sentence, remembering new vocabulary. In addition, WSP games improve students’ vocabulary learning activities. Students were actively involved in the teaching and learning process where they were more enthusiastic and interested in participating the vocabulary learning process. The results suggest that WSP games can be used as an alternative way of vocabulary learning for junior high school students.